ORIGINAL PAPER Identification of specific causes of unexplained heart failure with the use of endomyocardial biopsy - Bilińska, Zofia; Grzybowski, Jacek; Skwarek, Mirosław; Mazurkiewicz, Łukasz; Walczak, Ewa; Prochorec-Sobieszek, Monika; Deptuch, Tomasz; Chmielak, Zbigniew; Demkow, Marcin; Dębski, Artur; Witkowski, Adam; Wagner, Teresa; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
Cardiomyopathies are defined as a heart muscle disease of unknown origin. Identification of specific causes of the disease may influence on management and prognosis of the patients. The aim of the study was to assess the usefulness of endomyocardial biopsy in patients with unexplained heart failure. The study group consisted of 126 patients (97 male), mean age 36.3 years, who were referred for diagnostic endomyocardial biopsy in the years 1992-2003 with the diagnosis of dilated cardiomyopathy (KMR) 107 (84.9%) patients, restrictive heart diasease (RChS) – 9 (7.1%), idiopathic left ventricular dysfunction and unexplained arrhythmia – 8 (6.4%) and two patients with arrhythmogenic right ventricular dysplasia (1.6%). Bioptates were assessed with histopathology and immunohistology. We assessed survival in the study group. In 10% of the patients a specific diagnosis was made: myocarditis (ZMS) (n=10) and cardiac amyloidosis (n=3; types: AL-1, ATTR-1, unclassified-1). Based on combined clinical and endomyocardial biopsy data the diagnosis of specific heart disease was made in 24 (22.4%) patients with KMR (familial dilated cardiomyopathy (KMR-F), n=11; KMR associated with autoimmune disease (KMR+AUI), n=3; ZMS, n=9; ZMS+AUI, n=1) and in 4 (44.4%) patients with RChS (amyloidosis, n=3, constrictive pericarditis, n=1). In the remaining patients the diagnosis of idiopathic KMR was made (83 patients), and idiopathic restrictive cardiomyopathy (I-KMRe) in 5 patients. On univariate and multivariate analysis we showed that relative risk of death was higher in patients with amyloidosis and I-KMRe than in I-KMR (RR-22.12; p<0.0001). On multivariate analysis we also found that in patients with unexplained cardiomyopathy relative risk of death is higher in KMR+AUI (RR=4.89; p=0.039) and in patients at younger age (RR=0.66; p=0.018). To summarize, endomyocardial biopsy is a valuable method complementing the diagnostics of patients with unexplained heart failure, but percentage of specific diagnoses is low.